(untitled) (London Journal of Research In Humanities and Social Sciences, 2022)
The purposes of this research were: 1) to follow up the evaluation through Application of Health Impact assessment of Health Program and Development of Health and 2) to develop integration guidelines for the cooperation between the committee on the Improvement of the Quality of Life at district level and Sub-District Health Fund. The results shown: 1. The affective factors of the Integrated Enhancement of Health Program and Development of Health Mechanism at district level project were: 1) the aspect of Quality of Live Development committee from 11 members, 2) the aspect of environment, and 3) the aspect of mechanism supporting learning and participating processes, 2. The outcomes from 12 issues on working plans, 36 health promoting projects, and 11 online follow-up evaluation plans, 3. The results shown the quality of life of committees, the project at district level for integrating work, and the quality of life development committee for both district and sub-district levels, 4. There were 3 main innovations and 15 indicators. Moreover, there was a participation in working together that enhance responsibilities for working. In addition, the increasing of communities from sub-district levels could enhance more knowledge and innovations which were: 1) waste and environment management were proceeded for reducing foam, the establishment of Dansai Green Net creating for volunteers and organic vegetables farming groups, the establishment of agriculturist groups, and the customer projection of health products, 3) Dansai people always accept other project in order to cover more area including: (1) creating community 29 cases of care givers and the elderly care, (2) schools for elderly in 4 of 10 sub districts, and 2) guidelines for integration working on the Improvement of the Quality of Life. There was a support mechanism for learning and participating comprising 5 processes: Plan, Do, Check, Action and Share.